Young children working together. Cooperative learning effects on group work of children in Grade 1 of primary education. (June 2020) - Veldman, M.A.; Doolaard, S.; Bosker, R.J.; Snijders, T.A.B.
Abstract: It was examined whether cooperative learning within the Success for All (SfA) program led to improved group work behaviour of Grade 1 pupils. 168 pupils of six SfA schools and 144 pupils of four control schools participated. Positive and negative group work behaviour was observed during a group task, taking into account socioemotional ethos, group participation, and type of dialogue. Longitudinal multilevel analysis was used for the sequence of observed 20-s time intervals. SfA groups showed more positive and less negative group work behaviour compared to control groups, whilst controlling for several group characteristics. Results suggest that negative group work behaviour increased gradually during the whole task in control groups, while in SfA groups it increased only towards the end of the task. The findings indicate that cooperative learning may lead to improved group work behaviour of young pupils (6–7 years old). Highlights: Cooperative learning can lead to improved group work behaviour. Socioemotional ethos, participation and dialogue during a group task were observed. Intervention groups showed more positive and less negative group work behaviour. Developments of group work behaviour over time of the group task were explored.